Determinants of loan sizes in microfinance institutions: evidence from the Upper West Region of Ghana - Paul Bata Domanban (Cogent Economics & Finance, 2024)
AbstractThe impact of microfinance institution (MFIs) activities on household revenue in Northern Ghana is of significant importance, particularly in light of the high levels of poverty in the region. The objective of this research is to explore the factors that influence the amount of loans granted to beneficiaries of three microfinance systems, namely the informal, semi-formal, and formal institutions, in the Upper West Region. This seeks to identify the factors that influence households’ credit access from microfinance systems. To achieve this objective, primary data collected through a questionnaire was analysed using the Ordinary Least Squares (OLS) estimation technique. The model was initially run using data from the three microfinance systems and then separately estimated for each system. The study found consistency in the variables that affect the amount of loans received by borrowers across all systems. Age, household size, interest rate charged by the institution, and group membership were found to have a negative relationship with the amount of loan received by borrowers. The study recommends that microfinance institutions in the Upper West Region focus on reducing the geographical distance between the institution and potential borrowers, providing access to microfinance information and education, and extending repayment periods to increase the loan amount borrowers receive. Moreover, the study suggests that microfinance institutions in the region should factor in the influence of interest rates on loan accessibility and adopt measures to counteract any negative consequences.